Between-Day Reliability of Kinematic Variables Using Markerless Motion Capture for Single-Leg Squat and Single-Leg Landing Tasks - Matias Yoma; Lee Herrington; Chelsea Starbuck; Luis Llurda; Richard Jones (International Journal of Sports Physical Therapy)
# Background Markerless motion capture has the potential to repeatedly collect biomechanical data during activities associated with injuries. Few studies have assessed the reliability of this technology during single-leg tasks.